Spatiotemporal characterization of vanadium at the sediment–water interface of a multi-ecological lake - Wang, Yan; Zhou, Li; Zhang, Lan; You, Xiaohui; Li, Cai; Kong, Ming; Xiao, Jing; Chen, Xiang; Zhu, Dongdong; Hang, Xiaoshuai (The Science of the total environment, 2023)
As an emerging environmentally harmful metal, vanadium (V) deserves significant research attention due to its hazardous concentrations in aquatic environments. However, the research on the characterization of V in sediment–water interface (SWI) remains limited. In this study, seasonal sampling was conducted in algal- and macrophyte-dominated zones via the method of in situ high-resolution diffusive gradients in thin films (DGT). The concentration of dissolved V in water in algal-dominated regions (12 sites) exceeded the long-term ecotoxicology limit of 1.2 μg⋅L−1. Seasonal variations of chemical speciation of V were observed in three ecological sites. DGT-labile V at the SWI exhibited two basic patterns associated with eutrophic status, one showing sharply decreasing gradients in the vicinity of the SWI and the other showing the absence of diffusion gradient. Positive correlations were observed between the water-dissolved V and the DGT-labile V, indicating DGT-labile V is a sensitive indicator for the release of V from sediment into water. Moreover, the mobility of V was influenced by the reduction of Fe(hydr)oxides and complexation with organic matter, in particular, during periods of algal blooms. It is suggested that V contamination at the SWI of algal-dominated zones deserves additional attention. [Display omitted] •Spatiotemporal distribution of labile V in SWI is obtained in situ using high resolution methods of DGT.•The high mobility of V was caused by the reduction of Fe(hydr)oxides and DOM complexation associated with the algal bloom.•Positive correlations were found between V in water and the DGT-labile V and reducible V in the sediment.